The human responses and nursing diagnoses of head and neck cancer patients: literature review and synthesis of evidence - Susana Miguel; Cristina Mara Zamarioli; Emília Campos de Carvalho; Sílvia Caldeira (Universidade Católica Portuguesa, Instituto de Ciências da Saúde, 2019)
Introduction: Head and neck cancer is relatively common with a high morbidity rate due to the anatomical sites that surround and may result in psychosocial, physical, or functional effects. Knowledge about the human responses and the corresponding nursing diagnoses of head and neck cancer patients undergoing surgery, as listed on NANDA-I, seems scarce.  Aim: Review the literature on knowledge about the human responses and the corresponding nursing diagnoses of head and neck cancer patients undergoing surgery. Materials and Methods: Integrative literature review with a search on electronic databases: CINALH®, MEDLINE®, Nursing & Allied Health®, and Scopus®. Results: A total of 31 papers were included in this review and 72 human responses, categorized in 29 diagnoses. Most diagnoses are subjective, and the most frequent nursing diagnosis was disturbed body image.  Conclusion: Identifying the most frequent human responses of these patients facilitates nurses in providing adequate care and in developing further research aiming to improve diagnoses accuracy. Most diagnoses are subjective, and the clinical validation could improve the level of evidence and provide nurses with clinical indicators for clinical reasoning and effective planning and interventions. Particularly, differential validation is needed in these patients as similar diagnoses and confounding clinical indicators have been identified. Further research is needed to evaluate the subjective nursing diagnoses considering the similarity and specific defining characteristics in head and neck cancer.